A review of infrastructure project risk management - Ahmad Shukri, Yazid; Abdul Aziz, Abdullah; Mohd Rasid, Hussin (Medwell Journals, 2014)
Every successful project is highly dependent on the effective management of related risk exposures. The challenge is obviously the task of identifying and assessing the potential risks for projects to ensure that such risks could possibly be mitigated effectively with managerial efficiency. This study provides, a discussion of the various types of potential risks encountered during and throughout the entire course of project management. For that matter, managing infrastructure projects on a large scale, especially those projects which are being funded by Sukuk (Islamic Bond) can be rather complex primarily when dealing with both the project and Sukuk risks during the implementation of these projects. Rigorous review on earlier literature on risk-related were conducted to identify the different types of risk exposures. The types of risk can be identical and possibly encountered when managing infrastructure projects. With the identification of the various types of risk, the stakeholders (owners, joint venture partners, consultants, clients, sponsors and the financiers) could possibly have a much better understanding of the various types of risk involved in managing infrastructure projects, especially at the intiation stage of the projects and also during the preparation of the project charter for infrastructure projects which are being funded by the Islamic capital market.